Evaluation of the cancer stem cell marker NCAM expression In relation to prognostic parameters of renal cell carcinoma - BAN JUMAAH QASIM, (International Journal of Pharma and Bio Sciences, 2017)
A better understanding of the action of the cancer stem cell marker, neural cell adhesion molecule (NCAM), in tumor molecular pathways that cause tumor formation and growth may help in the development of new policies for the early detection and treatment of renal carcinoma. This study evaluated the expression of NCAM in relation to prognostic parameters of renal cell carcinoma (RCC) including histopathological type, Furhman nuclear grade, TNM stage, tumor size, renal vein invasion and perinephric fat invasion. Seventy paraffin blocks from cases of RCC who underwent nephrectomies were included in the present study. Thirty normal renal tissues were collected from autopsy cases as a control group. NCAM was assessed immunohistochemically in both control group and carcinoma tissues sections and the relations to prognostic parameters of RCC were calculated statistically. The difference in the expression of NCAM was highly significant between RCC cases and control group (p<0.001). There was highly statistically significant relation (p< 0.001) between NCAM expression and histopathological type, nuclear grade, tumor stage, renal vein invasion and perinephric fat invasion of RCC. In conclusion, NCAM may have an important role in renal cell carcinogenesis and may predict poor prognosis of RCC through its association with worse pathologic prognostic indicators of the disease.